Chapter 9 The housing careers of younger adults and intergenerational support in Germany's 'society of renters' - Lennartz, Christian (Taylor & Francis, 2019)
Through narrative interviews with younger adults and their parents , this paper explores how the housing transitions of younger adults, both within the rental sector and into homeownership, are shaped through intergenerational intra-family support in Germany's society of renters. Our fi ndings highlight the profound qualitative diff erences between regular transfers for establishing and retaining residential independence in the rental sector and inter vivos gifts for house purchase. Where the former support type is given and taken unconditionally, transfers for house purchase follow a diff erent logic and carry diff erent meanings. Being a necessary condition for property acquisition at young age, they have the power to completely rebalance family relations and undermine younger adults' autonomy accordingly. In an aggregate perspective, our study further suggests increasing socio-spatial inequalities within the younger generation which run along both class and spatial origin, sharply dividing the housing market opportunities of 'original Berliners' and those who have moved to the city from more affl uent regions in Germany.